Potential of Averrhoa bilimbi Leaf in Incision Wound Healing in Diabetic Rat Model - tahara; Aditya, Candra; Zurriyani, Zurriyani; Andri, Andri; Ika , Waraztuty; Said , Aandy Saida; Muhammad , Yani (Biology Department, Faculty of Mathematics and Natural Sciences, Sriwijaya University, 2024)
Diabetic wounds are a serious problem and need to be treated appropriately. One of the wound healing efforts is using the leaves of the Averrhoa billimbi (Abl). This study aims to examine the reduction in wound healing and histopathological images of wound-healing rats with Abl extract. The rat in the study were 2-3 months old, weighed 200-250 grams and were 12 male. The rat were divided into 3 groups: the control group (G1) received only distilled water, the group 10 µl extract (G2) and the group of diabetic mice received 10 l extract (G3). The treatment and skin tissue samples were obtained on day 8. The rats were digested with ether solution and skin incisions were made, followed by povidine idone administration. The study data were analyzed by analysis of variance (ANOVA). Statistical test results showed that the incision reduction was highest in G2, followed by G3 and G1 at 1.120 ± 0.156, 1.405 ± 0.007, 1.510 ± 0.028, respectively. Histopathological images of proliferative fibroblast cell counts and collagen density were higher in K3 than in K1. Based on the study results, it can be concluded that using 10 µl extract can heal cuts in diabetic rats.